2018
DOI: 10.3390/md16090339
|View full text |Cite
|
Sign up to set email alerts
|

Natural Product Chemistry of Gorgonian Corals of Genus Junceella–Part III

Abstract: The structures, names, bioactivities, and references of 82 natural products, including 48 new metabolites, purified from the gorgonian corals belonging to the genus Junceella are described in this review. All compounds mentioned in this review were obtained from Junceella fragilis, Junceella gemmacea, Junceella juncea, and Junceella sp., collected from tropical Indo-Pacific Ocean. Some of these compounds exhibited potential biomedical activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The sea whip gorgonian coral Junceella fragilis , a zooxanthella-containing species [20], has been demonstrated to have a wide structural diversity of interesting marine-origin briarane-type diterpenoids [7], and the compounds of this type were suggested originally to be produced by the host corals and not by its zooxanthellae [21]. In our continued study of Junceella fragilis collected in the waters of Taiwan, two previously unreported briaranes, fragilides P ( 1 ) and Q ( 2 ), were isolated along with two previously described analogues, robustolide F ( 3 ) and juncin Z ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sea whip gorgonian coral Junceella fragilis , a zooxanthella-containing species [20], has been demonstrated to have a wide structural diversity of interesting marine-origin briarane-type diterpenoids [7], and the compounds of this type were suggested originally to be produced by the host corals and not by its zooxanthellae [21]. In our continued study of Junceella fragilis collected in the waters of Taiwan, two previously unreported briaranes, fragilides P ( 1 ) and Q ( 2 ), were isolated along with two previously described analogues, robustolide F ( 3 ) and juncin Z ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among these compounds, 11,20-epoxybriaranes were proven to be a chemical marker for the gorgonian corals belonging to family Ellisellidae [6]. During the course of our research on new natural substances from the marine invertebrates distributed in the waters of Taiwan, a series of briarane-type diterpenoids were isolated from various octocorals belonging to the genera Junceella [7] and Briareum [8], and the compounds of this type were proven to possess various interesting bioactivities. Recently, we focused our ongoing studies on a gorgonian coral identified as Junceella fragilis .…”
Section: Introductionmentioning
confidence: 99%
“…Gorgonian corals of the genus Junceella (family Ellisellidae) [1][2][3] were proven to be the most important flagship species to produce 11,20-epoxybriarane diterpenoids, a chemical marker for the octocorals belonging to the family Ellisellidae [4,5] and the compounds of this type demonstrate a wide spectrum of biological properties, such as anti-inflammatory activity [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], immunomodulatory activity [21], insecticidal activity [22], cytotoxicity [23][24][25][26][27][28][29][30][31][32], anti-viral activity [6,33], anti-fouling activity [34][35][36][37], antifeedant [35], and anti-microbial activity [28,29,32,[38][39][40]. From the specimens of J. fragilis (Ridley 1884) collected off the waters of Taiwan, an area with high biodiversity at the intersection of the Kuroshio current and...…”
Section: Introductionmentioning
confidence: 99%
“…Gorgonian corals belonging to the genus Junceella (family Ellisellidae) [1][2][3], distributed abundantly in the coral reefs of tropical Indo-Pacific Ocean have been found to produce briarane diterpenoids, natural products of a marine origin, in abundance [4]. In our further research into the natural products of Junceella fragilis (Ridley 1884) ( Figure 1), which was distributed extensively in the waters of Southern Taiwan, have resulted in the isolation of three new 11,20-epoxybriaranes-fragilides U-W (1-3) along with two know compounds junceellonoid D (4) [5] and junceellin (5) [6][7][8][9][10][11][12][13][14][15] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%